Desenvolvimento de graxas lubrificantes utilizando pilhas de Li-Mn - Mazur, Douglas Luiz (2024)
This study investigated the recovery of lithium hydroxide from lithium-manganese dioxide button cells and its application in the synthesis of lubricating greases. For this purpose, discarded/unused batteries were processed, resulting in the extraction of lithium hydroxide, which, along with residual frying oil, produced a thickener for lubricating greases. Lithium greases were synthesized in different soap/base oil ratios, and a graphite grease was produced with the addition of 5% graphite recovered from the batteries. For the synthesis of lithium-potassium greases, commercial potassium hydroxide and the recovered lithium hydroxide were used. The lithium-potassium greases were also produced with different thickener/base oil ratios, with a variant containing graphite. SEM and AFM analysis of the greases revealed that all samples formed lubricating films on the applied surface, and the network structure of the thickener, which forms the characteristic structural skeleton of this type of grease, was also observed. Regarding the determination of the dropping point of the greases, it was found that the lithium-potassium grease had the highest dropping point, while the semi-fluid graphite lithium grease had the lowest. The absence of heavy metals in significant concentrations in the recovered lithium hydroxide reinforces its potential use in applications such as the synthesis of lubricating greases. The results indicate that the recovery of lithium hydroxide from used batteries is feasible and can be utilized in the manufacture of lubricating greases, contributing to a closed circular economy and environmental preservation.